Closed-loop quasi-orthogonal STBCs and their performance in multipath fading environments and when combined with turbo codes. - Toker, C.
Quasi-orthogonal space-time block codes (QO-STBCs) achieve full code rate at the expense of loss in diversity gain. We propose two feedback methods for QO-STBCs to achieve full diversity and full code rate. In the first method, signals radiated from various antennas are rotated by phasors according to feedback from the receiver, whereas the second method is based upon antenna weighting/selection. For high to moderate feedback error rates, it is demonstrated that the proposed methods outperform the quantized transmit beamformer. The performance improvement is also investigated for these closed-loop methods when the transmitted signal is error control coded.
Keywords: Antenna selection; Closed-loop quasiorthogonal STBC; Error control code; Feedback error rate; Multipath fading environment; Quantized transmit beamformer; Space-time block code; Turbo code